Nilai-Nilai Pendidikan Sosial Profetik Islam dalam Ideologi Pancasila - Muhammad Syukri Nawir Syukri; Athoillah Islamy (Al Hikmah: Jurnal Studi Keislaman, 2022)
The dichotomous and even confrontational paradigm of the relationship between Islamic teachings and Pancasila as a state ideology is still found in indonesian Muslims. This should not need to happen, because in fact the teachings of Islam and Pancasila have a universal intersection of values for the plurality of social life. This study aims to identify the value of Islamic prophetic social education in the construction of Pancasila. Quality research in the form of literature studies uses a normative-philosophical approach. Secondary data in the form of relevant journals, books, theses and dissertations. The three values in the idea of Islamic Prophetic Social Sciences formulated by Kuntowijoyo in the form of the values of humanization, liberation and transcendence became the analytical theory of the discussion of this research. These three values will be used to identify various prophetic social education values contained in the Pancasila precepts. The nature of this research approach is descriptive-analytic. Data analysis techniques include data reduction, data presentation, and data verification. The results showed that there was a dimension to the values of prophetic social education contained in Pancasila. First, the educational value of transcendence in the precepts of the Almighty godhead. The existence of the contained divine value can be a basis for values, paradigms and approaches in transforming the value of transcendence in all forms of educational activities. Second, the value of humanist education in the precepts of humanity and the precepts of unity. The existence of human values and unity can be a basin of values, paradigms and approaches to humanist educational activities that have an orientation of human empowerment of the urgency of science as well as positioning humans with all their potential. Third, the value of liberated education in the precepts of democracy and social justice. The existence of these values can be a basis for values, paradigms and approaches in liberation education that have an orientation to guide individuals so that they can be free from the intervention of any party or group that has a negative impact on social life.The theoretical implications of the findings of this study show that there is a meeting point for the content of universal values in Pancasila with the social teachings of Islamic religion. The limitations of this research can also be a lacuna (gap) for the next research, namely this research has not examined how the role of the government in disseminating the intersection of the social values of Islamic religion contained in the construction of Pancasila in the praxis life of Indonesian society.